On Some Geometric Methods in Mathematics and Mechanics (Global Journal of Science Frontier Research, 2017)
We give a survey of geometric methods used in papers and books of V.I. Arnold and V.V. Kozlov. They are methods of different normal forms, of some polyhedra, of small denominators and asymptotic expansions.
Keywords: geometric methods; normal form; asymptotic expansion; Painlev頥quations; Hamiltonian system